Analisis dampak Pembangunan Infrastruktur terhadap Pendapatan Rumah Makan dan Usaha oleh-oleh (Studi Kasus Pembangunan Jalan Tol Bangkinang-Pekanbaru - Akbar, Rahmad; Yetti, Dzulhijjah; Rahmayani, Merlia; Yelmi, Harmi; Nurbit, Nurbit; Kaido, Boris (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The development of Bangkinang-Pekanbaru toll road infrastructure has become the government's focus in efforts to improve connectivity and accelerate economic growth in the region. This research aims to analyze the impact of toll road construction on the income of restaurants and souvenir businesses before and after the operation of the toll road. This research was conducted using a quantitative approach with interviews with business owners. Data analysis uses a normality test to ensure the data is normally distributed and a difference test (T-test) to determine differences in respondents' income. The results of the research show that there is a significant difference in income between restaurants and souvenir businesses before and after the toll road. The results of the income normality test at restaurants are normally distributed data with a Sig value. 0.057 > 0.05, and income from the souvenir business is also normally distributed data with a Sig value. 0.281 > 0.05. The results of the Paired Sample T-test concluded that the restaurant obtained a Sig. (2-tailed) value of 0.000 < 0.05, so Ha was accepted "there was a difference in income at the restaurant before and after the Bangkinang-Pekanbaru toll road", whereas in The souvenir business obtained a Sig (2-tailed) value of 0.000 < 0.05, so Ha was accepted "there was a difference in income in the souvenir business before and after the Bangkinang-Pekanbaru toll road". This research contributes to further understanding of the relationship between toll road infrastructure development and local economic growth, especially in the context of income from restaurants and souvenir businesses.